Proceedings of the 12th International Conference on the Foundations of Digital Games 2017
DOI: 10.1145/3102071.3110568
|View full text |Cite
|
Sign up to set email alerts
|

Learning the patterns of balance in a multi-player shooter game

Abstract: A particular challenge of the game design process is when the designer is requested to orchestrate dissimilar elements of games such as visuals, audio, narrative and rules to achieve a speci c play experience. Within the domain of adversarial rst person shooter games, for instance, a designer must be able to comprehend the di erences between the weapons available in the game, and appropriately cra a game level to take advantage of strengths and weaknesses of those weapons. As an initial study towards computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…2a that the score of player 1 is spread over the entire spectrum, from extreme advantage over player 2 (scores near 1.0) to extreme disadvantage (scores near 0.0) and a balanced match (score of 0.5). Unlike [17], the score does not follow a normal distribution centered around 0.5; the distribution is rather uniform, with occurrences decreasing towards the edge cases. This points to a rich dataset with positive and negative examples of a balanced match.…”
Section: Training Datamentioning
confidence: 87%
See 2 more Smart Citations
“…2a that the score of player 1 is spread over the entire spectrum, from extreme advantage over player 2 (scores near 1.0) to extreme disadvantage (scores near 0.0) and a balanced match (score of 0.5). Unlike [17], the score does not follow a normal distribution centered around 0.5; the distribution is rather uniform, with occurrences decreasing towards the edge cases. This points to a rich dataset with positive and negative examples of a balanced match.…”
Section: Training Datamentioning
confidence: 87%
“…considering only the structural parts of the level [22] or the properties of weapons [10] in a vacuum. Compared to earlier work [17], the model introduced in this paper uses a much broader corpus of structurally and ludically complex levels and a diverse set of classes as its training set. It is also the first instance that uses such a multi-faceted computational model as a surrogate in generating aspects of a game's ruleset for specific levels and intended gameplay outcomes, while in [18] a similar surrogate model is used to drive the evolutionary adaptation of levels in order to balance a specific set of character classes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Given sufficient data, we can assume that a deep learning approach can assess whether game content match. For instance, deep learning was used to predict how levels and weapon parameters, combined, affect gameplay balance [109]; in [110], a similar mapping was used to adapt hand-authored or generated levels to be more balanced for specific matchups between character classes. It has been already shown that machine learning can capture level structures from gameplay videos [52], which can drive the generation of new levels.…”
Section: B Learning the Mapping Between Facetsmentioning
confidence: 99%
“…Based on the current state of digital games and its nature, as well as unfathomable speed of how computation power is being developed, the development of game contents is moving at similar pace as well [8]. Conventional content generation in digital games is a very rigorous and time-consuming process [9], much of its development pipeline requires multiple parts of development lifecycle and requires multiple expert to validate its output [10].…”
Section: Introductionmentioning
confidence: 99%